Wigner function description of a qubit-oscillator system - Allen, J.; Zagoskin, A.M. (Физика низких температур, 2013)
We derive the Bloch-type equations of motion for the Wigner function of a qubit nonlinearly coupled to a linear
oscillator, and investigate their usefulness in the quantum-classical transition regime.